122 A SWORD IN THE STONE - A STEMI AFTER MIAVR. (15th December 2022) - Scalia, Lorenzo; Francaviglia, Bruno; Calderone, Dario; Mauro, Maria Sara; Capodanno, Davide; Capranzano, Piera; Tamburino, Corrado
Abstract: Background: Minimally invasive aortic valve replacement (MIAVR) is defined as a surgical aortic valve replacement which involves smaller chest incisions (mini-sternotomy and right anterior mini-thoracotomy approaches) and minimized degree of surgical intrusiveness. Compared with conventional surgery, it has been shown to reduce postoperative mortality, providing faster and shorter recovery, requires less rehabilitations resources and consequently cost reduction. Even though MIAVR has considered as a safe and acceptable surgical technique, higher learning curve and requirement for re-training should be endorsed as procedural limitations. Among procedural related complications, embolic events still remain the most serious. Clinical case: A 70-year-old man, due to increasing dyspnea and chest pain came to emergency department. His medical history was notable for cigarettes smoke, dyslipidemia, non insuline dependent type 2 diabetes mellitus and hypertension. No abnormal electrocardiografic alterations. A transtoracic echocardiogram was performed showing, Left ventricular ejection fraction 50%, no wall motion abnormalities and thickened, ipomobil and calcified aortic valve cusps assessing a diagnosis of severe aortic stenosis. He was conducted to the cath-lab for a diagnostic coronary angiogram which showed a no-significant atherosclerotic disease. After Heart Team evaluation, MIAVR was the suitable and optimal management indicated for the patient. Four hours after ending surgical procedure, ST segment elevation suddenly appears on DII, DIII and aVF leads. Emergency coronary angiogram showed an acute occlusion of the proximal circumflex artery. After several unsuccessful attempts to cross the occlusion with different types of workhorse guidewires, we considered the cause of uncrossability was not a thrombus but a debris calcium embolus detached from valve apparatus. After failed attempts using FineCross, SuperCross 90° provided adequate support to gaining access and enhancing the penetrating power of guidewire; we put the guidewire distally through the Mo2 with partial flow regain. Then we proceeded to modify the plaque geometry with a NC balloon to help crossing guidewire through distal Cx. So we've passed over the lesion gaining Cx periphery with a Fielder XT guidewire and we've proceeded to prepare the lesion thorugh progressive NC balloon dilatations. At the end we've implanted a 3.5/15 mm DES on mid Cx. Conclusion: As MIAVR has being more common in the last twenty years, it is useful knowing how to manage any possible related peri-operative complications. Calcific valve is a very uncommon source of coronary debirs embolization. Coronary embolism is associated to worse outcomes: early diagnosis and revascularization must be required. Knowledge of CTO techniques and materials (guidewires, microcatheters) for a "non-CTO" dedicated operators could be useful in several scenarios, such as that encountered in the present case.